SISTEM INFORMASI KEUANGAN TAMAN PENDIDIKAN AL-QUR’AN (TPQ) NURUL HUDA KR.TAPEN BERBASIS WEB - Nurhayati Nurhayati; Sri Endang Anjarwani; Ariyan Zubaidi (Program Studi Teknik Informatika, Fakultas Teknik, Universitas Mataram, 2022)
Al-Qur'an Education Park of Nurul Huda Kr. Tapen manages and presents financial information using Microsoft Excel. The processing and presentation of financial information using Microsoft Excel raises several problems such as difficulties in data collection of financial income, difficulties in carrying out data collection for brothers and sisters, the problem of donor registration that is still done offline and difficulties in reporting financial institutions recapitulation. Therefore, a web-based financial information system is needed that can overcome these problems. In this research a system was developed that could facilitate agency employees in managing income including infaq input for santri siblings, expenditure management, printing incentive slips for each teacher and report on the institution's overall financial recapitulation. Financial information systems are built with HTML and PHP programming languages, using Codeigniter as framework, MySql as a database server and Xampp as a local server.